ANALISIS HIERARKI PROSES SEBAGAI PENENTUAN STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN - Susilo, Joko Hadi; Noor, Fauzian; Fatmawati, Dewi; Safitri, Silvia Niken (Trunojoyo University of Madura, 2023)
This research aims to determine sustainable tourism development strategies through several aspects, including diversification of tourism products, environmental preservation, involvement of local communities and human capital. This research method was carried out using a process hierarchy analysis approach to determine priority strategies from multi-criteria. Based on the results of this research, it can be concluded that the first priority aspect that must be implemented in developing sustainable tourism is human capital with the criteria of training as the first priority followed by skills/expertise, education and increasing experience. Tourism product diversification has as the second priority aspect with the first priority criteria being marketing and promotion followed by identification of potential new products, product development and launch, market analysis and consumer understanding. Involvement of local communities is the third priority aspect with the criteria of analyzing community conditions as the first priority, followed by tourism awareness groups/communities, cultural preservation and participation in decision making. Environmental preservation as the fourth priority aspect with the criteria for developing environmental policies and standards as the first priority, followed by environmental education and awareness, environmental management and restoration, evaluation of current environmental impacts. Meanwhile, the priority alternative as a sustainable tourism development strategy is the government, followed by the involvement of academics, the industrial world and the community.